As Diatribes de Epicteto, livro I - Aldo Dinucci (Classica Digitalia: Autores Gregos e Latinos: textos, 2020)
Epictet, stoic philosopher of the 1st century C.E., was the slave of Epaphroditus, an imperial secretary of Nero and Domitian. Despite his condition, he was able to attend the classes of Musônio Rufo. Later, after his release, he founded a school in Rome, which did not last long, since Domitian expelled the philosophers from the city in 89 C.E. Epictet then went to Nicopolis, where he founded another stoic school, with many students, among them important figures of the Roman Empire. Like Socrates, Epictet wrote nothing. His philosophy came to us through the notes of his disciple Lucio Flavio Arriano Xenophon, who recorded the teachings of Epictet in eight books, four of which were lost, which composed the Diatribes of Epictet. The work is prefaced by a letter from Arriano to a certain Lucius Gelius, in which Arriano affirms that the Diatribes are nothing more than transcriptions of the lessons of Epictet. That is the reason why the work has been attributed since antiquity to Epictet.